Spectrum of Causes of Cholestatic Jaundice in Neonates and Infants (Medical Forum Monthly, 2024)
Objective: To determine the causes of Cholestatic jaundice in infants and children.Study Design: Analytical study.Place and Duration of Study: This study was conducted at the Department of Pediatrics Naseer Teaching Hospital Peshawar from January 2015 to December 2018.Materials and Methods: A total of 25 patients presented with Cholestatic jaundice to the department of pediatrics were included in the study. All patients of both gender presented with jaundice in infancy. Data collected from all patients was put on a predesigned proforma. Data was analyzed on SPSS version 14.Results: A total of 25 patients diagnosed with Cholestatic jaundice were included in the study. Out of 25 patients 15 (60%) were male and 10(40%) were female. Biliary atresia was the most common cause present in 7(28%) cases, followed by galactosemia and progressive familial intrahepatic cholestasis (PFIC) which were 4(16%) cases each. Cytomegalovirus (CMV) infection was found in 3(12%) cases. Alagille syndrome and choledochal cyst were diagnosed in 2(8%) cases each. Caroli disease, Neonatal sepsis and Neonatal hemochromatosis was present in 1(4%) case each.Conclusion: From this study we concluded that Cholestatic jaundice is a common problem in infants and has diverse causes both medical and surgical. Timely diagnosis is important for the prognosis of disease.